Ali ibn Abi Talib: The Caliphate Conflicts of Ali ibn Abi Talib and Their Relevance to Modern Islamic Politics - Siregar, Asri Yanti; Amril M (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This article discusses the leadership of Ali ibn Abi Talib as the fourth caliph in Islamic history, a period marked by political turmoil and internal conflict following the death of Uthman ibn Affan. This crisis was highlighted by major events such as the Battle of the Camel, the Battle of Siffin, and the emergence of the Kharijites. Using a descriptive-qualitative approach based on literature review, this study examines how Ali applied principles of justice, equality, and moral responsibility in responding to these challenges. The findings show that despite the brevity and trials of his rule, Ali remains a model of integrity and steadfast leadership, offering valuable lessons in governing during times of crisis.